THE ROLE OF THE SUMENEP PALACE MUSEUM IN PRESERVING LOCAL CULTURE FROM 2010 TO 2020: Peranan Museum Keraton Sumenep dalam Pelestarian Budaya Lokal Tahun 2010-2020 - Aulia fitriany; M. Khusni Mubarok; Rina Andriani (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This historical study aims to explore the transformation of the Sumenep Kingdom into the present-day Keraton Sumenep, to identify the role of the museum in preserving local Madurese culture from 2010 to 2020, and to analyze the impact of cultural preservation efforts on the educational relevance for younger generations in Sumenep. Employing historical research methodology, the study utilized data from observations, interviews with museum staff and educators, and documentation of cultural artifacts and programs. Findings reveal that the transformation of the kingdom into a palace reflects a significant historical continuity, reinforced through preserved royal heritage such as weaponry, royal attire, and traditional texts. The museum has actively implemented educational outreach, including school visits and cultural exhibitions, as a means of engaging youth and transmitting cultural values. It also serves as a platform for living traditions, such as the annual ritual of jamasan pusaka and traditional performing arts. These initiatives contribute to sustaining cultural identity amid the pressures of globalization. The study underscores the museum's dual function as a historical institution and an educational catalyst, particularly in shaping local identity and intergenerational cultural literacy. Its efforts suggest a sustainable model of cultural preservation rooted in community participation and formal education..